(untitled) (Kaumodaki: Journal of Multidisciplinary Studies, 2022)
Ecophilosophy, as a holistic view of nature is implied in the identification of nature and human relation with definite sense of harmony. Pragmatic naturalism, as the combination of reason and fact in nature, works in a common ground of harmony in nature as the practical part and the part of observing the human wisdom to and towards nature. This study probes into Thoreau’s poetic imagination about nature and how Thoreau, as the transcendental naturalist, uses nature as a powerful means of understanding human essence to natural world. Also it examines how he has observed nature, though the life cannot be imagined detached from nature and natural force, as free and ontologically capable to exist with balanced relation with nature and society. Nature is self-regulating being but with unity for the sense of harmony through ecosystem and pragmatic aspect. As the ecological wisdom of realizing nature, he has seen nature as a metaphor of ‘book’ and thinks that nature provides the lessons to humans greater than anything else really could. This study is based on an identified problem - how Thoreau, through his poems, tends to illustrate the idea that nature is an already existing truth and guiding principle of human understanding and nature-human harmony.